Enhancing optical character recognition capabilities for Bengali script: the development and evaluation of Bengali CharNet - Kamal, Rizvy Ahmed (Brac University, 2024)
This project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.